Evaluation of crossbred cows and crossbred bulls - Schalles, R.R.; Zoellner, K.O.; Meier, R.J. (Kansas State University. Agricultural Experiment Station, 2011)
Crossbred cows are common but interested in using crossbred bulls is recent. Little information is available on use of crossbred bulls, so advice and recommendations have been based on genetic principles rather than research. Nine mating combinations are reported here from using purebred and high grade Hereford, Santa Gertrudis, and crosses of Hereford and Santa Gertrudis cows and bulls.
Keywords: Beef; Crossbred cows; Crossbred bulls